2006
DOI: 10.1145/1147376.1147378
|View full text |Cite
|
Sign up to set email alerts
|

Scientific formats for object-relational database systems

Abstract: Commercial database management systems (DBMSs) have historically seen very limited use within the scientific computing community. One reason for this absence is that previous database systems lacked support for the extensible data structures and performance features required within a high-performance computing context. However, database vendors have recently enhanced the functionality of their systems by adding object extensions to the relational engine. In principle, these extensions allow for the representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 1 publication
0
4
0
4
Order By: Relevance
“…Cohen et al use meteorological data to compare the efficiency of using a vector data type called VArray and Oracle nested tables against three different scientific purpose data containers: netCDF, HDF4, and HDF5 [21]. They show that HDF5 is the most efficient storage mechanism for large data volumes of meteorological data.…”
Section: Related Workmentioning
confidence: 99%
“…Cohen et al use meteorological data to compare the efficiency of using a vector data type called VArray and Oracle nested tables against three different scientific purpose data containers: netCDF, HDF4, and HDF5 [21]. They show that HDF5 is the most efficient storage mechanism for large data volumes of meteorological data.…”
Section: Related Workmentioning
confidence: 99%
“…An experimental study 5 showed that, even if using array primitives in RDBMSs, native file formats outperformed the relational implementation by a factor of 20 to as much as 80. Proposed scientific DBMSs 6,23 provide multidimensional arrays as first-class types, aiming to bridge the gap between DBMSs and native files in the process.…”
Section: Data and Process Integrationmentioning
confidence: 99%
“…Relational database management systems (RDBMSs) have repeatedly shown that they are very efficient, scalable and successful in hosting types of data which have formerly not been anticipated to be stored inside relational databases such as complex objects [21] , spatio-temporal data [22] and XML data [23] . In addition, RDBMSs have shown its ability to handle vast amounts of data very efficiently using its powerful indexing mechanisms.…”
Section: Introductionmentioning
confidence: 99%